2015
DOI: 10.1159/000373953
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Stimulates Jejunum Chloride Secretion via an Akt-Mediated Pathway in Intact Female Mice

Abstract: Background/Aims: We have previously shown that daily subcutaneous injections with the naturally occurring phytoestrogen genistein (600 mg genistein/kg body weight/day, 600G) results in a significantly increased basal intestinal chloride, Cl-, secretion (Isc, a measure of transepithelial secretion) in intact C57BL/6J female mice after 1-week of treatment, compared to controls (DMSO vehicle injected). Removal of endogenous estrogen via ovariectomy (OVX) had no effect on the 600G-mediated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
1
1
Order By: Relevance
“…Interestingly, genistein diet rescued this in female ob/ob mice but not in males. We have previously noted sex-dependent mechanisms of action of genistein in ovariectomized mice [44]. The Na Our data is not consistent with Serhan et al [45], demonstrating that insulin increases glucose uptake with reductions in Na + /K + -ATPase expression, and increased expression of SGLT1 in Caco-2 cells and rat jejunum.…”
Section: +contrasting
confidence: 81%
“…Interestingly, genistein diet rescued this in female ob/ob mice but not in males. We have previously noted sex-dependent mechanisms of action of genistein in ovariectomized mice [44]. The Na Our data is not consistent with Serhan et al [45], demonstrating that insulin increases glucose uptake with reductions in Na + /K + -ATPase expression, and increased expression of SGLT1 in Caco-2 cells and rat jejunum.…”
Section: +contrasting
confidence: 81%
“…However, the role of sex hormones (mainly estrogen) on the enzymes involved in the intracellular signaling, i.e., kinases, is very controversial. Indeed, while some authors demonstrated that estrogen could modulates kinases proteins expression such as Akt (Bhuiyan et al, 2011; Turdi et al, 2015), PKG (Word and Cornwell, 1998) and PKC (Hunter and Korzick, 2005; Hunter et al, 2007), others suggest that there is no modulation by estrogen on these kinases (Teede et al, 2001; Cao et al, 2015; Leung et al, 2015). Taken together, these studies showed that the relationship between the expression of kinases and estrogen levels is very complex which becomes a limiting factor for the use of estrogen therapy in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…Assessments of transepithelial short circuit current (I sc , μA/cm 2 ) were obtained as described previously [11,18], with 0.3 cm 2 exposed surface area of freshly excised jejunum. Short circuit current was measured via an automatic voltage clamp (VCC-600, Physiologic Instruments, San Diego, CA) [11,18].…”
Section: Bioelectric Measurement Of Intestinal Secretionmentioning
confidence: 99%
“…Assessments of transepithelial short circuit current (I sc , μA/cm 2 ) were obtained as described previously [11,18], with 0.3 cm 2 exposed surface area of freshly excised jejunum. Short circuit current was measured via an automatic voltage clamp (VCC-600, Physiologic Instruments, San Diego, CA) [11,18]. All tissue segments were maintained in 1 μM indomethacin which served to reduce the tissue exposure to endogenously generated prostanoids due to tissue handling [19].…”
Section: Bioelectric Measurement Of Intestinal Secretionmentioning
confidence: 99%
See 1 more Smart Citation